2016
DOI: 10.1002/adfm.201604733
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency and High Open Circuit Voltage in Quasi 2D Perovskite Based Solar Cells

Abstract: An important property of hybrid layered perovskite is the possibility to reduce its dimensionality to provide wider band gap and better stability. In this work, 2D perovskite of the structure (PEA)2(MA)n–1PbnBr3n+1 has been sensitized, where PEA is phenyl ethyl‐ammonium, MA is methyl‐ammonium, and using only bromide as the halide. The number of the perovskite layers has been varied (n) from n = 1 through n = ∞. Optical and physical characterization verify the layered structure and the increase in the band gap.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
189
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(196 citation statements)
references
References 29 publications
7
189
0
Order By: Relevance
“…Quasi-2D perovskites have demonstrated interesting lightemitting, [1][2][3] lasing, [4,5] and photovoltaic [6][7][8] properties with superior stabilities. Essentially, quasi-2D perovskites are formed with the Ruddlesden-Poper perovskite (RPP) nanoplates separated by www.advmat.de www.advancedsciencenews.com CW 980 nm excitation.…”
Section: Doi: 101002/adma201901240mentioning
confidence: 99%
See 1 more Smart Citation
“…Quasi-2D perovskites have demonstrated interesting lightemitting, [1][2][3] lasing, [4,5] and photovoltaic [6][7][8] properties with superior stabilities. Essentially, quasi-2D perovskites are formed with the Ruddlesden-Poper perovskite (RPP) nanoplates separated by www.advmat.de www.advancedsciencenews.com CW 980 nm excitation.…”
Section: Doi: 101002/adma201901240mentioning
confidence: 99%
“…[20] On the other hand, it has been found that the edge states can be formed in 2D perovskites with light-emitting properties below the bandgap. Polarizationdependent up-conversion PL studies reveal that the gap states experience the orbit-orbit interaction through Coulomb polarization to form spatially extended states toward developing multi-photon up-conversion light emission in quasi-2D perovskites.Quasi-2D perovskites have demonstrated interesting lightemitting, [1][2][3] lasing, [4,5] and photovoltaic [6][7][8] properties with superior stabilities. We should note that an up-conversion ASE was indeed observed at 720 nm in inorganic 3D perovskite (CsPbI 3 ) nanoplates under the infrared pulse laser excitation of 1200 nm.…”
mentioning
confidence: 99%
“…The generic molecular formula of 2D RP lead iodide perovskites can be written as (L) 2 A n−1 Pb n I 3n+1 where L + is alkylammonium cation-typically phenylethylamine (C 8 H 11 N, PEA) and butylamine (n-BA), A + is monovalent organic cations such as CH 3 NH 3 + , and the n value is the number of Pb−I octahedral layers between adjacent spacers. [21][22][23][24][25][26][27] 2D Ruddlesden-Popper (RP) perovskite solar cells have manifested superior operation durability yet inferior charge transport compared to their 3D counterparts. [19] Besides, the bandgap (E g ) of 2D perovskites increases with narrowing the thickness of the quantum wells (i.e., decreasing the n value), which is incompatible with making use of the full solar spectrum.…”
mentioning
confidence: 99%
“…Quan et al [49] supposed that lower mobility leads to slower charge extraction, followed by carriers accumulation which enables higher V OC . Meanwhile, Cohen et al [93] inferred that lower mobility of 2D perovskite relieves the carrier accumulation at selective contact, and therefore reduces the quenching at interface and results in higher V OC . The V OC could potentially be further improved through transport materials selecting and contact interface engineering [6,14].…”
mentioning
confidence: 99%